Comparison of lateral episiotomy, traditional midwifery without episiotomy, and hands-off techniques delivery on pelvic floor function - Jingjing Gong; Lili Xing; Xiaodan Li; Xiaona Wang; Huijuan Chen (BMJ Publishing Group, 2021)
Background: Prolonged vaginal delivery times and episiotomy are associated with damage to the muscles of the pelvic floor, and with complications that include postpartum sexual dysfunction and urinary stress incontinence. This study was to compare the pelvic floor function among postpartum women who underwent three midwifery practices during labor: lateral episiotomy, traditional midwifery without episiotomy, and hands-off techniques delivery. Methods: We included 320 primipara who were full-term pregnancy and underwent vaginal delivery in Department of Obstetrics, Peking University People's Hospital, China. 117 women had episiotomy during labor and were classified into the lateral episiotomy group; 103 had traditional midwifery without episiotomy and were classified into the traditional midwifery practice group; and 100 experienced hands-off techniques during labor and were classified into the hands-off techniques delivery group. The duration of the second stage of labor, and postpartum pelvic floor muscle strength were compared between the three study groups. Results: There were no significant differences between the three groups for the duration of the second stage of labor and postpartum pelvic floor muscle strength (P ​> ​0.05). However, the incidence of postpartum urinary stress incontinence and sexual dysfunction in the hands-off techniques delivery group was significantly lower than in the lateral episiotomy groups and the traditional midwifery practice group (P ​< ​0.01). Conclusions: Hands-off techniques delivery could reduce damage to the pelvic floor and improve the quality of life for women after delivery.